Work related musculoskeletal disorders among surgeons working in a tertiary care hospital in Kathmandu, Nepal - Vaidya, Anira; Sainju, Nayan Kamal; Joshi, Sunil Kumar (International Journal of Occupational Safety and Health, 2017)
Background: Musculoskeletal disorders are common work-related health problems affecting professionals in many sectors. Surgeons are among the most vulnerable as they have to work for long hours in unfavorable posture. Objective: Aim of this study was to determine both prevalence of work related musculoskeletal disorders and types of ailments among surgeons of different sub-specialties in a tertiary care hospital in Kathmandu. Methods: In This cross sectional study was conducted in Bir Hospital, a tertiary care hospital in Kathmandu. A total of 50 surgeons of different sub-specialties were surveyed. Self-reported questionnaires included i) socio-demographic information, ii) Dutch Musculoskeletal Questionnaire on ergonomic hazards and iii) Nordic musculoskeletal disorders questionnaire on pain and discomfort. Data were analyzed using SPSS version 20. Result: Respondents were 40 male and 10 female surgeons with mean age of 38.9 years. Forty-four respondents (88%) reported that their job usually require them to stand for long hours, and41 (82%) also reported that they would work in the same posture for long period of time. In addition, 43 (86%) also reported that they would have to bend their trunk slightly during their job. Thirty-five respondents (70%) reported having at least one musculoskeletal disorder. Twenty-three (65.7%) surgeons had to miss their job at least once during last 12 month of which nineteen (54.3%) missed them in last 7 days. Conclusion: This survey showed that various musculoskeletal ailments were common among surgeons of all sub-specialties in our hospital which is likely one of the common and a serious occupational hazards in this population.